Wiedza o zdrowiu a aktywność fizyczna w stylu życia uczestników Uniwersytetów Trzeciego Wieku na przykładzie Wrocławia = Knowledge about health and physical activity in life style among students of Universities of the Third Age on the example of Wroclaw - Jarecka, Paulina; Fąk, Tadeusz (Journal of Education, Health and Sport, 2016)
Jarecka Paulina, Fąk Tadeusz. Wiedza o zdrowiu a aktywność fizyczna w stylu życia uczestników Uniwersytetów Trzeciego Wieku na przykładzie Wrocławia = Knowledge about health and physical activity in life style among students of Universities of the Third Age on the example of Wroclaw. Journal of Education, Health and Sport. 2016;6(8):842-851. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.212485 http://ojs.ukw.edu.pl/index.php/johs/article/view/4085 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 01.12.2016. Wiedza o zdrowiu a aktywność fizyczna w stylu życia uczestników Uniwersytetów Trzeciego Wieku na przykładzie Wrocławia Knowledge about health and physical activity in life style among students of Universities of the Third Age on the example of Wroclaw Paulina Jarecka1, Tadeusz Fąk2 1 Katedra Pedagogiki Kultury Fizycznej, Akademia Wychowania Fizycznego we Wrocławiu 2 Instytyt Turystyki, Wyższa Szkoła Bankowa we Wrocławiu Słowa kluczowe: aktywność fizyczna, Uniwersytet Trzeciego Wieku, wiedza o zdrowiu Key words: physical activity, University of the Third Age, knowledge about health Streszczenie Celem przeprowadzonych badań jest wyjaśnienie zależności między wiedzą o uwarunkowaniach zdrowia a aktywnością fizyczną uczestników Uniwersytetów Trzeciego Wieku we Wrocławia. Badania przeprowadzono w 2016 roku metodą sondażu diagnostycznego, w ramach której posłużono się techniką ankiety. Wyniki badań wskazują na występowanie istotnej zależności między wiedzą o uwarunkowaniach zdrowia a aktywnością fizyczną respondentów. Analiza prezentowanego materiału badawczego pozwala stwierdzić, że zarówno poziom wiedzy jak i aktywność fizycznej respondentów jest zadawalający. Abstract The goal of this research is explanation of dependencies between knowledge about health determinants and physical activity of the participants of University of the Third Age operating in Wroclaw. The study was conducted in 2016 using method of diagnostic survey in which poll technique was utilized. The results of research indicate an occurrence of significant relationship between knowledge about health determinants and physical activity of respondents. Presented research materials analysis allow to conclude, that both the level of knowledge and physical activity of respondents are satisfactory.